Influence of wall heterogeneity on nanoscopically confined polymers. Issue 2 (14th December 2018) - Pastore, Raffaele; David, Alessio; Casalegno, Mosè; Greco, Francesco; Raos, Guido
Abstract : We investigate via molecular dynamics simulations the behaviour of a polymer melt confined between surfaces with increasing spatial correlation (patchiness) of weakly and strongly interacting sites. Abstract : We investigate via molecular dynamics simulations the behaviour of a polymer melt confined between surfaces with increasing spatial correlation (patchiness) of weakly and strongly interacting sites. Beyond a critical patchiness, we find a dramatic dynamic decoupling, characterized by a steep growth of the longest relaxation time and a constant diffusion coefficient. This arises from dynamic heterogeneities induced by the walls in the adjacent polymer layers, leading to the coexistence of fast and slow chain populations. Structural variations are also present, but they are not easy to detect. Our work opens the way to a better understanding of adhesion, friction, rubber reinforcement by fillers, and many other open issues involving the dynamics of polymeric materials on rough, chemically heterogeneous and possibly "dirty" surfaces.